\section{Definitions} \generic{$\lm$ Notation:} $\lm$ notation is used to define functions, and looks like $(\lm ~ \text{input} ~ . ~ \text{output})$. \\ Consider the following statement: $$ I = \lm a . a $$ This tells us that $I$ is a function that takes its input, $a$, to itself. We'll call this the \textit{identity function}. \\ To apply functions, put them next to their inputs. We'll omit the usual parentheses to save space. $$ (I~\star) = (\lm \tzm{b}a. a)~\tzmr{a}\star = \star \begin{tikzpicture}[ overlay, remember picture, out=225, in=315, distance=0.5cm ] \draw[->,gray,shorten >=5pt,shorten <=3pt] (a.center) to (b.center); \end{tikzpicture} $$ Functions are left-associative: If $A$ and $B$ are functions, $(A~B~\star)$ is equivalent to $((A~B)~\star)$. As usual, we'll use parentheses to group terms if we want to override this order: $(A~(B~\star)) \neq (A~B~\star)$ \\ In this handout, all types of parentheses ( $(), [],$ etc ) are equivalent. \vfill \generic{$\beta$-Reduction:} $\beta$-reduction is a fancy name for \say{simplifying an expression.} We've already done it once above. Let's make another function: $$ M = \lm f . f f $$ $M$ takes a function as an input and calls it on itself. What is $(M~I)$? $$ (M~I) = ((\lm \tzm{b}f.f f)~\tzmr{a}I) = (I~I) = ((\lm \tzm{d}a.a)~\tzmr{c}I) = I \begin{tikzpicture}[ overlay, remember picture, out=225, in=315, distance=0.5cm ] \draw[->,gray,shorten >=5pt,shorten <=3pt] (a.center) to (b.center); \draw[->,gray,shorten >=5pt,shorten <=3pt] (c.center) to (d.center); \end{tikzpicture} $$ We cannot reduce this any further, so we stop. Our expression is now in \textit{$\beta$-normal form}. \vfill \pagebreak \problem{} Reduce the following expressions: \begin{itemize} \item $I~I$ \item $I~I~I$ \item $(\lm a .(a~a~a)) ~ I$ \item $(\lm a . (\lm b . a)) ~ M ~ I$ \end{itemize} \vfill \pagebreak \generic{Currying:} Lambda functions are only allowed to take one argument, but we can emulate multivariable functions through \say{currying.} \vspace{1ex} Before we begin, let's review \textit{function composition}. With \say{normal} functions, composition is written as $(f \circ g)(x) = f(g(x))$. This means \say{$f$ of $g$ of $x$}. \vspace{1ex} To demonstrate currying, we'll make a function $C$ in lambda calculus, which takes two functions ($f$ and $g$), an input $x$, and produces $f$ applied to $g$ applied to $x$. \\ In other words, we want a $C$ so that $C~f~g~x = f~(g~x)$ \vspace{1ex} We'll define this $C$ as follows: $$ C = \lm f . (\lm g . (\lm x . f(g(x)))) $$ \vspace{1ex} This looks awfully scary, so let's take this expression apart. \\ C is a function that takes one argument ($f$) and returns a function (underlined): $$ C = \lm f .(~~\tzm{a} \lm g . (\lm x . f(g(x))) \tzm{b}~~) \begin{tikzpicture}[ overlay, remember picture ] \node[below = 1ex] at (a.center) (aa) {}; \node[below = 1ex] at (b.center) (bb) {}; \path[draw = gray] (aa) to (bb); \end{tikzpicture} $$ \vspace{1ex} The function it returns does the same thing. It takes an argument $g$, and returns \textit{another} function: $$ C = \lm f . (~~ \lm g . (~~\tzm{a} \lm x . f(g(x)) \tzm{b}~~) ~~) \begin{tikzpicture}[ overlay, remember picture ] \node[below = 1ex] at (a.center) (aa) {}; \node[below = 1ex] at (b.center) (bb) {}; \path[draw = gray] (aa) to (bb); \end{tikzpicture} $$ \vspace{1ex} This last function $\lm x. f(g(x))$ takes one argument, and returns $f(g(x))$. Since this function is inside the previous two, it has access to their arguments, $f$ and $g$. \vspace{2ex} So, currying allows us to create multivariable functions by nesting single-variable functions. \\ As you saw above, such expressions can get very long. We'll use a bit of shorthand to make them more palatable. If we have an expression with repeated function definitions, we'll combine their arguments under one $\lm$. \vspace{1ex} For example, $$ C = \lm f . (\lm g . (\lm x . f(g(x)))) $$ will become $$ C = \lm fgx.(~f(g(x))~) $$ \vspace{1ex} This is only notation. \textbf{Curried functions are not multivariable functions!} They must be evaluated one variable at a time, just like their un-curried version. Substituting all curried variables in one go may cause errors, as you'll see below. \problem{} Evaluate $C~M~I~\star$ \\ Then, evaluate $C~I~M~I$ \\ \hint{Place parentheses first. Remember, function application is left-associative.} \vfill \pagebreak \definition{$\alpha$-equivalence} We say two functions are \textit{$\alpha$-equivalent} if they differ only by the names of their variables: $I = \lm a.a = \lm b.b = \lm \heartsuit . \heartsuit = ...$ \generic{$\alpha$-Conversion:} Variables inside functions are \say{scoped.} We must take care to keep separate variable separate. For example, take the functions \\ $A = \lm a b . a$ \\ $B = \lm b . b$ \vspace{2ex} We could say that $(A~B) = \lm b . (\lm b . b)$, and therefore $$ ((A~B)~I) = (~ (\lm \tzm{b}b . (\lm b . b))~\tzmr{a}I ~) = \lm I . I \begin{tikzpicture}[ overlay, remember picture, out=225, in=315, distance=0.5cm ] \draw[->,gray,shorten >=5pt,shorten <=3pt] (a.center) to (b.center); \end{tikzpicture} $$ Which is, of course, incorrect. $\lm I . I$ is not a valid function. \vspace{2ex} Notice that both $A$ and $B$ use the input $b$. However, each $b$ is \say{bound} to a different function. The two $b$s are therefore distinct. \vspace{2ex} Let's rewrite $B$ as $\lm c . c$ and try again: $$ (A~B) = \lm b . ( \lm c . c) = \lm bc . c $$ Now, we correctly find that $(A~B~I) = (\lm bc . c)~I = \lm c . c = B = I$. \problem{} Let $C = \lm abc.b$ \\ Reduce $(C~a~c~b)$. \begin{solution} I'll rewrite $(C~a~c~b)$ as $(C~a_1~c_1~b_1)$: \begin{align*} C = (\lm abc.b) &= (\lm a.\lm b.\lm c.b) \\ (\lm a.\lm b.\lm c.b)~a_1 &= (\lm b.\lm c.b) \\ (\lm b.\lm c.b)~c_1 &= (\lm c.c_1) \\ (\lm c.c_1)~b_1 &= c_1 \end{align*} \end{solution} \vfill \problem{} Reduce $((\lm a.a)~\lm bc.b)~d~\lm eg.g$ \begin{solution} $((\lm a.a)~\lm bc.b)~d~\lm eg.g$ \\ $= (\lm bc.b)~d~\lm eg.g$ \\ $= (\lm c.d)~\lm eg.g$ \\ $= d$ \end{solution} \vfill \pagebreak